Secondary battery and electric device
Patent Information
- Application Number
- CN202280095095.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-11-25
AI Technical Summary
然而,在现有技术中面临的问题是:在提高二次电池的动力学性能时,往往难以兼顾二次电池的能量密度;在提高二次电池的能量密度时,往往影响二次电池的动力学性能以及使用寿命
Smart Images

Figure CN119032437B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to a secondary battery and an electrical device. Background Technology
[0002] In recent years, rechargeable batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. With the increasingly widespread application of rechargeable batteries, significant challenges have been placed on their performance, such as the need to balance energy density, kinetic performance, and lifespan. However, the current technology faces the problem that improving the kinetic performance of rechargeable batteries often fails to maintain energy density, while increasing energy density often negatively impacts both kinetic performance and lifespan. Summary of the Invention
[0003] This application was developed in view of the above-mentioned technical problems, and its purpose is to provide a secondary battery and an electrical device that enables the secondary battery to have high energy density while taking into account high safety performance, good dynamic performance and cycle performance.
[0004] A first aspect of this application provides a secondary battery, including a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer formed on at least one surface of the negative current collector, the negative electrode film layer having a first surface away from the negative current collector and a second surface disposed opposite to the first surface, the thickness of the negative electrode film layer is denoted as H, a region from the second surface of the negative electrode film layer to a thickness range of 0.3H is denoted as a first region of the negative electrode film layer, and a region from the first surface of the negative electrode film layer to a thickness range of 0.3H is denoted as a second region of the negative electrode film layer, the first region including a first active material, the first active material including a first carbon-based material and a second carbon-based material, the first carbon-based material having a porous structure, and the second carbon-based material including artificial graphite.
[0005] The inventors discovered in their research that by simultaneously including a first carbon-based material and a second carbon-based material in the first region of the negative electrode film, with the first carbon-based material having a porous structure and the second carbon-based material including artificial graphite, the negative electrode sheet can have high compaction density, low volume change, and high active ion transport speed. This enables the secondary battery to have high energy density while also having high safety performance, good kinetic performance, and good cycle performance.
[0006] In any embodiment of this application, the second carbon-based material includes artificial graphite with secondary particles; optionally, the proportion of artificial graphite with secondary particles in the second carbon-based material is greater than or equal to 50%. When the second carbon-based material contains an appropriate proportion of artificial graphite with secondary particles, it can increase the active ion channels in the negative electrode film layer and shorten the active ion insertion path, thereby further improving the kinetic performance of the secondary battery, and also reducing battery polarization and the occurrence of side reactions, thus enabling the secondary battery to achieve both good cycle performance and kinetic performance.
[0007] In any embodiment of this application, the interlayer spacing of the 002 crystal planes of the second carbon-based material is greater than that of the 002 crystal planes of the first carbon-based material. By adjusting the interlayer spacing of the 002 crystal planes of the second carbon-based material in the first region of the negative electrode film to be greater than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0008] In any embodiment of this application, the graphitization degree of the second carbon-based material is less than that of the first carbon-based material. By adjusting the graphitization degree of the second carbon-based material in the first region of the negative electrode film to be less than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0009] In any embodiment of this application, the specific capacity of the second carbon-based material is less than that of the first carbon-based material. By combining a first carbon-based material with high capacity with a second carbon-based material including artificial graphite in the first region of the negative electrode film, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0010] In any embodiment of this application, the interlayer spacing of the 002 crystal plane of the second carbon-based material is less than or equal to 0.33600 nm, and can be selected as 0.33571 nm to 0.33600 nm. When the interlayer spacing of the second carbon-based material is within the above range, it has high surface stability, thereby reducing the occurrence of side reactions and facilitating the rapid insertion and extraction of active ions, which is beneficial to improving the active ion transport performance of the negative electrode film. Therefore, the secondary battery can achieve both high energy density and good cycle performance and kinetic performance.
[0011] In any embodiment of this application, the specific capacity of the second carbon-based material is greater than or equal to 353 mAh / g, and can be selected as 355 mAh / g-365 mAh / g. When the specific capacity of the second carbon-based material is within the above range, it can improve the energy density of the secondary battery on the one hand, and on the other hand, it can also make the second carbon-based material have good active ion transport performance, thereby also helping to improve the kinetic performance of the secondary battery.
[0012] In any embodiment of this application, the compacted density of the second carbon-based material powder under a pressure of 20000N is 1.75 g / cm³. 3 -2.05g / cm 3 The option is 1.78 g / cm³. 3 -2.00g / cm 3 When the compaction density of the second carbon-based material powder is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. In addition, it is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film, improving the active ion and electron transport performance, improving the wetting and retention characteristics of the negative electrode film in the electrolyte, and thus improving the cycle performance and kinetic performance of the secondary battery.
[0013] In any embodiment of this application, the second carbon-based material comprises artificial graphite, and the surface of the artificial graphite does not have a carbon coating layer. Artificial graphite has a relatively stable surface; when its surface does not have a carbon coating layer, it is beneficial to maintain its low side-reaction activity, which helps to reduce the occurrence of side reactions and thus further improves the cycle performance of the secondary battery.
[0014] In any embodiment of this application, the volume distribution particle size Dv10 of the second carbon-based material is 6μm-12μm, and can be selected as 6.5μm-11.5μm.
[0015] In any embodiment of this application, the volume distribution particle size Dv50 of the second carbon-based material is 12.0 μm-22.0 μm, and can be optionally 13.5 μm-20.5 μm;
[0016] When the volume distribution particle size Dv10 and / or Dv50 of the second carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. It can also reduce the specific surface area of the second carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery. In addition, it can form a reasonable pore structure with the first carbon-based material in the negative electrode film, improving the wetting and retention characteristics of the negative electrode film to the electrolyte.
[0017] In any embodiment of this application, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is ≤1.65, and can be selected as 0.90-1.65.
[0018] When the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, its particle packing performance is better, which is beneficial to improving the compaction density of the negative electrode film and the energy density of the secondary battery. In addition, it is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0019] In any embodiment of this application, the tap density of the second carbon-based material is 0.85 g / cm³. 3 -1.30g / cm 3 0.90 g / cm³ is an option. 3 -1.30g / cm 3 When the tap density of the second carbon-based material is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0020] In any embodiment of this application, the specific surface area of the second carbon-based material is 1.0 m². 2 / g-2.9m 2 / g, can be selected as 1.2m 2 / g-2.5m 2 / g. When the specific surface area of the second carbon-based material is within the above range, it is beneficial to reduce the occurrence of side reactions and reduce the consumption of active ions by the SEI film formation, thereby helping the secondary battery to achieve both high initial coulombic efficiency and good cycle performance; in addition, the second carbon-based material also has good active ion intercalation and deintercalation performance, which can improve the kinetic performance of the secondary battery.
[0021] In any embodiment of this application, the first carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm. 2 The pore structure may optionally include one or more pores with an area of 0.15 μm. 2 -2.0μm 2 The pore structure. When the first carbon-based material includes a pore structure with the aforementioned pore area, the pore structure can reserve the necessary expansion space for changes in particle volume, thereby further reducing the risk of particle breakage and the generation of new interfaces, which in turn can reduce the occurrence of side reactions and improve the cycle performance of the secondary battery.
[0022] In any embodiment of this application, the first carbon-based material includes an outer region and an inner region located inside the outer region. The outer region refers to the area formed by extending 0.25L from the particle surface of the first carbon-based material into the particle interior, where L refers to the minor axis length of the first carbon-based material particle. The total pore area of the outer region is denoted as S1, and the total pore area of the inner region is denoted as S2, where S2>S1. When the first carbon-based material also satisfies S2>S1, the initial coulombic efficiency and cycle performance of the secondary battery can be improved.
[0023] In any embodiment of this application, 1.5 ≤ S2 / S1 ≤ 500, and optionally, 2 ≤ S2 / S1 ≤ 450. When S2 / S1 is also within the above range, the secondary battery can better balance high energy density and good cycle performance.
[0024] In any embodiment of this application, the area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm. 2 The option is less than or equal to 0.10 μm. 2 By controlling the area of the pore structure in the outer region of the first carbon-based material within the aforementioned range, the outer region of the first carbon-based material can have a dense structure, thereby effectively improving the structural stability of the first carbon-based material and minimizing the penetration of electrolyte into the pore structure inside the particles of the first carbon-based material, thus effectively improving the cycle performance of the secondary battery.
[0025] In any embodiment of this application, the internal region of the first carbon-based material includes one or more particles with an area greater than or equal to 0.15 μm. 2 The pore structure may optionally include one or more pores with an area of 0.15 μm. 2 -2.0μm 2 The porous structure. By including the above-mentioned porous structure in the internal region of the first carbon-based material, on the one hand, the rolling pressure of the negative electrode sheet can be effectively reduced, particle damage can be effectively reduced, and sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, thereby reducing the risk of breakage of the first carbon-based material particles. On the other hand, the compaction density of the negative electrode film can be increased, and the volume change of the negative electrode film can be buffered.
[0026] In any embodiment of this application, the specific surface area of the first carbon-based material is 0.7 m². 2 / g-1.8m 2 / g, optional 0.8m 2 / g-1.6m 2 / g. The first carbon-based material has a lower specific surface area, which can reduce the consumption of active ions during SEI film formation and improve the initial coulombic efficiency and cycle performance of the secondary battery.
[0027] In any embodiment of this application, the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and can be optionally 10.0 μm-20.0 μm;
[0028] In any embodiment of this application, the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-35.0 μm, and can be optionally 17.0 μm-32.0 μm.
[0029] When the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. It can also reduce the specific surface area of the first carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery. In addition, it can form a reasonable pore structure with the second carbon-based material in the negative electrode film, improving the wetting and retention characteristics of the negative electrode film to the electrolyte.
[0030] In any embodiment of this application, the ratio of (Dv90-Dv10) / Dv50 of the first carbon-based material is ≤1.50, and can be selected as 0.7-1.40.
[0031] When the (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, its particle packing performance is better, which is conducive to improving the compaction density of the negative electrode film and thus further improving the energy density of the secondary battery. In addition, it is also conducive to forming a reasonable pore structure with the second carbon-based material in the negative electrode film, improving the active ion and electron transport performance, improving the wetting and retention characteristics of the negative electrode film to the electrolyte, and improving the cycle performance and kinetic performance of the secondary battery.
[0032] In any embodiment of this application, the compacted density of the first carbon-based material powder under a pressure of 20000N is 1.75 g / cm³. 3 -1.95g / cm 3 1.80g / cm³ is an optional value. 3 -1.90g / cm 3 .
[0033] When the compaction density of the first carbon-based material powder is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0034] In any embodiment of this application, the tap density of the first carbon-based material is 0.80 g / cm³.3 -1.50g / cm 3 0.85g / cm³ is an optional value. 3 -1.45g / cm 3 .
[0035] When the tap density of the first carbon-based material is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the second carbon-based material of the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0036] In any embodiment of this application, the graphitization degree of the first carbon-based material is ≥93.5%, and can be optionally 93.8%-98%.
[0037] When the degree of graphitization of the first carbon-based material is within the above range, its specific capacity is higher, which is beneficial to improving the energy density of the secondary battery.
[0038] In any embodiment of this application, the OI value of the first carbon-based material powder is 8-18, optionally 8-16. When the OI value of the first carbon-based material powder is within the above range, it is beneficial for receiving active ions and also beneficial for reducing the thickness expansion rate of the negative electrode film.
[0039] In any embodiment of this application, the specific capacity of the first carbon-based material is ≥354 mAh / g, optionally between 354 mAh / g and 370 mAh / g. This can improve the energy density of the secondary battery.
[0040] In any embodiment of this application, two diffraction peaks exist in the peak pattern of the X-ray diffraction pattern of the first carbon-based material within the range of 2θ of 25.5°-27.5°. When two diffraction peaks exist in the peak pattern of the X-ray diffraction pattern of the first carbon-based material within the range of 2θ of 25.5°-27.5°, it is beneficial to improve the energy density and kinetic performance of the secondary battery.
[0041] In any embodiment of this application, among the two diffraction peaks, the one with the smaller 2θ is designated as the first peak, and the one with the larger 2θ is designated as the second peak, and the ratio of the peak intensity of the first peak to the peak intensity of the second peak is 10:90-40:60. When the ratio of the peak intensity of the first peak to the peak intensity of the second peak is within the above range, it is beneficial for the secondary battery to better balance high energy density and good kinetic performance.
[0042] In any embodiment of this application, the mass percentage of the first carbon-based material in the first active material is ≥20wt%, and can be selected as 30wt%-70wt%. When the mass percentage of the first carbon-based material is within the above range, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0043] In any embodiment of this application, the second region includes a second active material, which includes a third carbon-based material. Optionally, the surface of the third carbon-based material has a carbon coating layer, which is beneficial to improving the kinetic performance of the secondary battery.
[0044] In any embodiment of this application, the third carbon-based material comprises graphite having a carbon coating on its surface. Optionally, the graphite comprises at least one of artificial graphite and natural graphite.
[0045] In any embodiment of this application, the third carbon-based material includes artificial graphite with a carbon coating layer on its surface, and the artificial graphite includes secondary particles; optionally, the proportion of the secondary particles in the artificial graphite is ≥50%. When the third carbon-based material contains an appropriate proportion of secondary particles, it can increase the active ion channels in the negative electrode film layer and shorten the active ion insertion path, thereby further improving the kinetic performance of the secondary battery, and also reducing battery polarization and the occurrence of side reactions, thus enabling the secondary battery to maintain good cycle performance.
[0046] In any embodiment of this application, the interlayer spacing of the 002 crystal plane of the second carbon-based material is smaller than that of the 002 crystal plane of the third carbon-based material. The larger interlayer spacing of the third carbon-based material is beneficial for the rapid insertion and extraction of active ions. Therefore, by adjusting the interlayer spacing of the 002 crystal plane of the second carbon-based material to be smaller than that of the 002 crystal plane of the third carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0047] In any embodiment of this application, the graphitization degree of the second carbon-based material is greater than that of the third carbon-based material. The third carbon-based material has a lower graphitization degree and a larger interlayer spacing, which is beneficial for the rapid insertion and extraction of active ions. Therefore, by adjusting the graphitization degree of the second carbon-based material to be greater than that of the third carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0048] In any embodiment of this application, the specific capacity of the second carbon-based material is greater than that of the third carbon-based material. The third carbon-based material has a smaller specific capacity and a larger interlayer spacing, which is conducive to the rapid insertion and extraction of active ions, thereby further improving the kinetic performance of the secondary battery; the second carbon-based material and the first carbon-based material have higher specific capacities, which is also conducive to the secondary battery achieving both high energy density and good kinetic performance.
[0049] In any embodiment of this application, the powder compaction density of the second carbon-based material at 20,000 N pressure is greater than that of the third carbon-based material at 20,000 N pressure. By adjusting the powder compaction density of the second carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0050] In any embodiment of this application, the powder compaction density of the first carbon-based material at 20,000 N pressure is greater than that of the third carbon-based material at 20,000 N pressure. By adjusting the powder compaction density of the first carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0051] In any embodiment of this application, the volume distribution particle size Dv50 of the second carbon-based material is greater than that of the third carbon-based material. By adjusting the volume distribution particle size Dv50 of the second carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0052] In any embodiment of this application, the volume distribution particle size Dv50 of the first carbon-based material is greater than that of the third carbon-based material. By adjusting the volume distribution particle size Dv50 of the first carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0053] In any embodiment of this application, the volume distribution particle size Dv50 of the third carbon-based material is 10.0 μm-22.0 μm, and optionally 11.5 μm-20.0 μm. When the volume distribution particle size Dv50 of the third carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of the third carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery.
[0054] In any embodiment of this application, the (Dv90-Dv10) / Dv50 of the third carbon-based material is ≤1.65, and can be selected as 0.90-1.65. When the (Dv90-Dv10) / Dv50 of the third carbon-based material is within the above range, its particle packing performance is better, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial for the negative electrode film to have a suitable pore distribution, improving the wetting and retention characteristics of the negative electrode film to the electrolyte, and improving the cycle performance and kinetic performance of the secondary battery.
[0055] In any embodiment of this application, the OI value of the third carbon-based material powder is 2.0-6.5, optionally 2.0-6.0. The third carbon-based material has a low OI value, and the particles have active ion insertion ports in all directions, thereby enabling it to quickly receive active ions from the positive electrode, thus further improving the kinetic performance of the secondary battery.
[0056] In any embodiment of this application, the powder compaction density of the third carbon-based material under a pressure of 20000N is 1.65 g / cm³. 3 -2.00g / cm 3 The option is 1.68g / cm³. 3 -1.98g / cm 3 When the compaction density of the third carbon-based material powder is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery; it is also beneficial to have a suitable pore distribution, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0057] In any embodiment of this application, the tap density of the third carbon-based material is 0.85 g / cm³. 3 -1.25g / cm 3 0.90 g / cm³ is an option. 3 -1.25g / cm 3When the tap density of the third carbon-based material is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial for the negative electrode film to have a suitable pore distribution, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film in the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0058] In any embodiment of this application, the graphitization degree of the third carbon-based material is ≤96%, and can be selected as 90.5%-95.5%. When the graphitization degree of the third carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film, thereby helping the secondary battery to achieve both high energy density and good kinetic performance.
[0059] In any embodiment of this application, the specific surface area of the third carbon-based material is 0.9 m². 2 / g-2.5m 2 / g, can be selected as 0.95m 2 / g-2.45m 2 / g. When the specific surface area of the third carbon-based material is within the above range, it is beneficial for the rapid insertion and extraction of active ions, improves the kinetic performance of the secondary battery, and can also reduce the consumption of active ions by the SEI film formation, thereby improving the first coulombic efficiency of the secondary battery.
[0060] In any embodiment of this application, the specific capacity of the third carbon-based material is 340 mAh / g-360 mAh / g, optionally 345 mAh / g-360 mAh / g. Having a specific capacity within this range allows the third carbon-based material to possess good active ion transport performance, improving the kinetic performance of the secondary battery, while also helping the secondary battery achieve a relatively high energy density.
[0061] In any embodiment of this application, the first region and / or the second region further include a silicon-based material. The silicon-based material can improve the pore structure in the negative electrode film, facilitating electrolyte wetting and retention, and enhancing the kinetic performance of the secondary battery; it can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery.
[0062] In any embodiment of this application, both the first region and the second region include silicon-based materials, and the mass percentage of the silicon-based material in the first region is less than or equal to the mass percentage of the silicon-based material in the second region. This is beneficial for improving the wetting characteristics of the negative electrode film layer to the electrolyte, improving the transport performance of active ions, and improving the cycle performance and / or kinetic performance of the secondary battery.
[0063] In any embodiment of this application, the intermediate region located between the first region and the second region includes the first active material and / or the second active material.
[0064] A second aspect of this application provides an electrical device that includes the secondary battery of the first aspect of this application.
[0065] The electrical device of this application includes the secondary battery provided in this application, and therefore has at least the same advantages as the secondary battery. Attached Figure Description
[0066] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0067] Figure 1 This is a schematic diagram of one embodiment of the negative electrode sheet of this application.
[0068] Figure 2 This is a schematic diagram of another embodiment of the negative electrode sheet of this application.
[0069] Figure 3 This is a schematic diagram of another embodiment of the negative electrode sheet of this application.
[0070] Figure 4 This is a schematic diagram of a cross-sectional image of the particles of the first carbon-based material of this application.
[0071] Figure 5 This is a schematic diagram of one embodiment of the secondary battery of this application.
[0072] Figure 6 This is an exploded view of one embodiment of the secondary battery of this application.
[0073] Figure 7 This is a schematic diagram of one embodiment of the battery module of this application.
[0074] Figure 8 This is a schematic diagram of one embodiment of the battery pack of this application.
[0075] Figure 9 yes Figure 8 An exploded view of an embodiment of the battery pack shown.
[0076] Figure 10 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application.
[0077] In the accompanying drawings, the figures may not be drawn to scale. The reference numerals are explained as follows: 1 Battery pack, 2 Upper casing, 3 Lower casing, 4 Battery module, 5 Secondary battery, 51 Housing, 52 Electrode assembly, 53 Cover plate, 10 Negative electrode sheet, 101 Negative electrode current collector, 102 Negative electrode film, 102a First surface, 102b Second surface, 1021 First region, 1022 Second region, 1023 Intermediate region, 200 First carbon-based material, 201 External region, 202 Internal region. Detailed Implementation
[0078] The embodiments of the secondary battery and power-consuming device of this application are hereby disclosed in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0079] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0080] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0081] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0082] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0083] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0084] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0085] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0086] Unless otherwise specified, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in this application.
[0087] Unless otherwise specified, in this application, the term "active ion" refers to ions that can be inserted and extracted back and forth between the positive and negative electrodes of a secondary battery, including but not limited to lithium ions.
[0088] In this application, the terms "multiple" or "various" refer to two or more kinds of things.
[0089] The inventors discovered that the key to improving the cycle performance of rechargeable batteries lies in balancing the battery's energy density and charging capacity. Currently, most methods to improve the kinetic performance of the negative electrode are to reduce the weight of the negative electrode film coating or decrease the compaction density of the negative electrode film. However, numerous studies have shown that these methods only improve the kinetic performance of the battery in the initial stage of charging, and have no significant effect on improving the kinetic performance in the later stage of charging. This results in the rechargeable battery's kinetic performance not being effectively improved, and may even prevent the battery from being charged at high rates. In addition, the energy density of the rechargeable battery will also be significantly reduced.
[0090] When the energy density of a secondary battery is increased by, for example, by increasing the compaction density of the negative electrode film, it often leads to a deterioration in the battery's kinetic and cycle performance. In addition, the volume change of the negative electrode film also increases, which in turn increases the risk of electrolyte breakage and affects the safety performance of the secondary battery.
[0091] Therefore, it is currently difficult for secondary batteries to simultaneously achieve high energy density, high safety performance, and good cycle performance and kinetic performance.
[0092] The inventors conducted extensive research and ingeniously improved the composition of the negative electrode film, breaking through the aforementioned bottleneck.
[0093] Specifically, the first aspect of the embodiments of this application provides a secondary battery.
[0094] This application does not impose any particular limitation on the type of secondary battery; for example, the secondary battery can be a lithium-ion battery. Typically, a secondary battery includes a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the secondary battery, active ions repeatedly insert and extract between the positive and negative electrode, and the electrolyte acts as a conductor for these active ions. This application does not impose any particular limitation on the type of electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solutions). Secondary batteries using electrolyte solutions, and some secondary batteries using solid electrolytes, may also include a separator membrane disposed between the positive and negative electrode to provide isolation.
[0095] [Negative electrode plate]
[0096] Figures 1 to 3 This is a schematic diagram illustrating an embodiment of the negative electrode sheet of this application. For example... Figures 1 to 3As shown, the negative electrode 10 includes a negative current collector 101 and a negative electrode film 102 formed on at least one surface of the negative current collector 101. The negative electrode film 102 has a first surface 102a away from the negative current collector 101 and a second surface 102b opposite to the first surface 102a. The thickness of the negative electrode film 102 is denoted as H. The region from the second surface 102b to a thickness of 0.3H is denoted as the first region 1021 of the negative electrode film, and the region from the first surface 102a to a thickness of 0.3H is denoted as the second region 1022 of the negative electrode film. The first region 1021 includes a first active material, which includes a first carbon-based material and a second carbon-based material. The first carbon-based material has a porous structure, and the second carbon-based material includes artificial graphite. The thickness H of the negative electrode film refers to the thickness of the negative electrode film located on one side of the negative current collector.
[0097] In this application, "the first carbon-based material has a porous structure" means that the first carbon-based material has a porous structure that can be directly observed from a cross-sectional image (e.g., a scanning electron microscope image with a magnification of 1000x), that is, the porous structure in the raw materials used to prepare the first carbon-based material is not completely filled.
[0098] The inventors discovered in their research that by simultaneously including a first carbon-based material and a second carbon-based material in the first region of the negative electrode film, with the first carbon-based material having a porous structure and the second carbon-based material including artificial graphite, the negative electrode sheet can have high compaction density, low volume change, and high active ion transport speed. This enables the secondary battery to have high energy density while also having high safety performance, good kinetic performance, and good cycle performance.
[0099] Through in-depth research, the inventors discovered that the first carbon-based material has a porous structure and is easily deformable during cold pressing. When it is located in the first region of the negative electrode film, it can effectively reduce the rolling pressure of the negative electrode sheet, thereby effectively reducing particle damage and the occurrence of side reactions. The porous structure of the first carbon-based material can also reserve the necessary expansion space for particle volume changes, reducing the risk of particle breakage and the generation of new interfaces, thus reducing the occurrence of side reactions. In addition, when the first carbon-based material is located in the first region of the negative electrode film, it can also reduce its adverse effects on the dynamic performance of the secondary battery and give full play to its advantages of high capacity and high compaction density, thereby improving the energy density of the secondary battery.
[0100] The second carbon-based material includes artificial graphite, which has good kinetic properties. This is beneficial for increasing the speed at which active ions are inserted into the first region of the negative electrode film, thereby improving the active ion transport performance of the negative electrode film and enhancing the kinetic performance of the secondary battery. At the same time, the second carbon-based material can also form a good pore structure with the first carbon-based material, which has a porous structure, thereby improving the wetting and retention characteristics of the negative electrode film with electrolyte and reducing the volume change of the negative electrode film.
[0101] Therefore, the negative electrode sheet provided in this application can have a good pore structure, while having high solid density, low volume change and high active ion transport rate, and can enable the secondary battery to have high energy density while taking into account high safety performance as well as good kinetic performance and cycle performance.
[0102] In some embodiments, the second carbon-based material comprises artificial graphite with secondary particles. Optionally, the proportion of artificial graphite with secondary particles in the second carbon-based material is greater than or equal to 50%, for example, it can be 60%-95%, 60%-100%, 65%-85%, 70%-100%, 75%-90%, 75%-85%, 80%-100%, 80%-90%, 85%-95%, or 90%-100%. When the second carbon-based material contains an appropriate proportion of artificial graphite with secondary particles, the active ion channels in the negative electrode film layer can be increased, and the active ion insertion path can be shortened, thereby further improving the kinetic performance of the secondary battery. It can also reduce battery polarization and the occurrence of side reactions, thus enabling the secondary battery to achieve both good cycle performance and kinetic performance.
[0103] In this application, the proportion of artificial graphite secondary particles in the second carbon-based material refers to: taking a test sample randomly in the negative electrode film layer, taking multiple test areas randomly in the test sample, acquiring images of multiple test areas using a scanning electron microscope, and statistically analyzing the proportion of artificial graphite secondary particles in the first region of the negative electrode film layer in each image to the total number of particles in the second carbon-based material. The average of multiple statistical results is the proportion of artificial graphite secondary particles in the second carbon-based material.
[0104] In some embodiments, the interlayer spacing of the 002 crystal planes of the second carbon-based material is greater than that of the first carbon-based material. The larger interlayer spacing of the second carbon-based material facilitates rapid insertion and extraction of active ions, while the smaller interlayer spacing of the first carbon-based material results in higher specific capacity. Therefore, by adjusting the interlayer spacing of the 002 crystal planes of the second carbon-based material in the first region of the negative electrode film to be greater than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0105] In some embodiments, the graphitization degree of the second carbon-based material is lower than that of the first carbon-based material. The lower graphitization degree of the second carbon-based material results in a larger interlayer spacing, which is beneficial for the rapid insertion / extraction of active ions. Conversely, the higher graphitization degree of the first carbon-based material results in a higher specific capacity. Therefore, by adjusting the graphitization degree of the second carbon-based material in the first region of the negative electrode film to be lower than that of the first carbon-based material, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0106] In some embodiments, the specific capacity of the second carbon-based material is less than that of the first carbon-based material. By combining a first carbon-based material with high capacity with a second carbon-based material including artificial graphite in the first region of the negative electrode film, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0107] In some embodiments, the interlayer spacing of the 002 crystal plane of the second carbon-based material is less than or equal to 0.33600 nm, and can be selected as 0.33571 nm-0.33600 nm. When the interlayer spacing of the second carbon-based material is within the above range, it has high surface stability, thereby reducing the occurrence of side reactions and facilitating the rapid insertion and extraction of active ions, which is beneficial to improving the active ion transport performance of the negative electrode film. Therefore, the secondary battery can achieve both high energy density and good cycle performance and kinetic performance.
[0108] In some embodiments, the specific capacity of the second carbon-based material is greater than or equal to 353 mAh / g, and can be selected as 355 mAh / g-365 mAh / g. When the specific capacity of the second carbon-based material is within the above range, it can improve the energy density of the secondary battery on the one hand, and on the other hand, it can also make the second carbon-based material have good active ion transport performance, thereby also helping to improve the kinetic performance of the secondary battery.
[0109] In some embodiments, the compacted density of the second carbon-based material at a pressure of 20,000 N is 1.75 g / cm³. 3 -2.05g / cm 3 The option is 1.75g / cm³. 3 -2.00g / cm 3 1.78 g / cm 3 -2.00g / cm 3 When the compaction density of the second carbon-based material powder is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. In addition, it is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film, improving the active ion and electron transport performance, improving the wetting and retention characteristics of the negative electrode film in the electrolyte, and thus improving the cycle performance and kinetic performance of the secondary battery.
[0110] In some embodiments, the second carbon-based material comprises artificial graphite, and the surface of the artificial graphite does not have a carbon coating layer. Artificial graphite has a relatively stable surface, and when its surface does not have a carbon coating layer, it helps maintain its low side-reaction activity, reducing the occurrence of side reactions and thus further improving the cycle performance of the secondary battery.
[0111] The inventors further discovered that when the second carbon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as improving at least one of the energy density, safety performance, kinetic performance, and cycle performance of the secondary battery.
[0112] In some embodiments, the volume distribution particle size Dv10 of the second carbon-based material is 6μm-12μm, and optionally 6.5μm-11.5μm.
[0113] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 12.0 μm-22.0 μm, and optionally 13.5 μm-20.5 μm.
[0114] When the volume distribution particle size Dv10 and / or Dv50 of the second carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. It can also reduce the specific surface area of the second carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery. In addition, it can form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, reduce the volume change of the negative electrode film, and improve the cycle performance and safety performance of the secondary battery.
[0115] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is ≤1.65, and can be selected as 0.90-1.65. When the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, its particle packing performance is better, which is beneficial to improving the compaction density of the negative electrode film and increasing the energy density of the secondary battery. In addition, it is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, reduce the volume change of the negative electrode film, and thus improve the cycle performance, safety performance and / or kinetic performance of the secondary battery.
[0116] In some embodiments, the tap density of the second carbon-based material is 0.85 g / cm³. 3 -1.30g / cm 3 0.90 g / cm³ is an option. 3 -1.30g / cm 3When the tap density of the second carbon-based material is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, reduce the volume change of the negative electrode film, and thus improve the cycle performance, safety performance and / or kinetic performance of the secondary battery.
[0117] In some embodiments, the specific surface area of the second carbon-based material is 1.0 m². 2 / g-2.9m 2 / g, can be selected as 1.2m 2 / g-2.5m 2 / g. When the specific surface area of the second carbon-based material is within the above range, it is beneficial to reduce the occurrence of side reactions and reduce the consumption of active ions by the SEI film formation, thereby helping the secondary battery to achieve both high initial coulombic efficiency and good cycle performance; in addition, the second carbon-based material also has good active ion intercalation and deintercalation performance, which can improve the kinetic performance of the secondary battery.
[0118] In some embodiments, the first carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm. 2 The pore structure may optionally include one or more pores with an area of 0.15 μm. 2 -2.0μm 2 The pore structure. When the first carbon-based material includes a pore structure with the aforementioned pore area, the pore structure can reserve the necessary expansion space for changes in particle volume, thereby further reducing the risk of particle breakage and the generation of new interfaces, which in turn can reduce the occurrence of side reactions and improve the cycle performance of the secondary battery.
[0119] In some embodiments, the first carbon-based material includes an outer region and an inner region located inside the outer region. The outer region refers to the region formed by extending 0.25L from the particle surface of the first carbon-based material into the particle interior, where L refers to the minor axis length of the first carbon-based material particle. The total pore area of the outer region is denoted as S1, and the total pore area of the inner region is denoted as S2, where S2>S1.
[0120] When the first carbon-based material also satisfies S2>S1, it further exhibits the following characteristics: a large number and / or large pore size in the internal region, and a small number and / or small pore size in the external region. The pore structure in the internal region of the first carbon-based material effectively reduces the rolling pressure on the negative electrode, effectively reduces particle damage, and reserves the necessary expansion space for particle volume changes. This reduces the risk of particle breakage and the formation of new interfaces, thereby effectively reducing the occurrence of side reactions. The small number and / or small pore size in the external region of the first carbon-based material allows for a stable structure in the particles and minimizes electrolyte penetration into the pore structure within the particles, further reducing side reactions and decreasing the consumption of active ions by the formation of the SEI film inside the particles. Therefore, when the first carbon-based material also satisfies S2>S1, it can improve the initial coulombic efficiency and cycle performance of the secondary battery.
[0121] In some embodiments, 1.5 ≤ S2 / S1 ≤ 500, 2 ≤ S2 / S1 ≤ 450, 2.2 ≤ S2 / S1 ≤ 400, 2.4 ≤ S2 / S1 ≤ 300, 2.5 ≤ S2 / S1 ≤ 250, 2.6 ≤ S2 / S1 ≤ 200, 2.8 ≤ S2 / S1 ≤ 150, and 3.0 ≤ S2 / S1 ≤ 100. Further research by the inventors revealed that when S2 / S1 also falls within the above ranges, the secondary battery can better balance high energy density and good cycle performance.
[0122] In this application, the total pore area S1 of the outer region and the total pore area S2 of the inner region of the first carbon-based material can be obtained by testing a cross-sectional image of the first carbon-based material.
[0123] In this application, the cross-sectional image of the first carbon-based material includes a cross-sectional image passing through the center of the first carbon-based material particles. The "particle center" refers to the range within a radius of 0.1 μm extending from the geometric center of the particle towards the particle surface.
[0124] In this application, the minor axis length of a particle refers to the minimum value when the line connecting two points on the particle surface passes through the geometric center of the particle.
[0125] Figure 4 This is a schematic diagram of a cross-sectional image of a particle of the first carbon-based material 200 of this application, and the cross-sectional image passes through the center of the particle of the first carbon-based material 200. Figure 4 As shown, L represents the short axis length of the particles of the first carbon-based material 200. The region formed by extending 0.25L from the surface of the particles of the first carbon-based material 200 into the particle interior is the outer region 201, and the region inside the outer region 201 is the inner region 202.
[0126] The cross-section of the first carbon-based material can be prepared using a cross-section polisher (e.g., the IB-09010CP argon ion cross-section polisher from JEOL, Japan); then, referring to JY / T010-1996, the cross-section of the first carbon-based material can be scanned using a scanning electron microscope (e.g., the Sigma 300 scanning electron microscope from ZEISS, Germany); finally, the total pore area S1 of the outer region and the total pore area S2 of the inner region of the first carbon-based material can be calculated using image processing software (e.g., AVIZO).
[0127] In some embodiments, the minor axis length L of the first carbon-based material particle satisfies L≥5.5μm, and optionally, 6μm≤L≤20μm, 8μm≤L≤20μm, 8μm≤L≤18μm, or 8μm≤L≤16μm.
[0128] In some embodiments, the area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm. 2 The option is less than or equal to 0.10 μm. 2 Further research by the inventors revealed that by controlling the area of the pore structure in the outer region of the first carbon-based material within the aforementioned range, the outer region of the first carbon-based material can possess a dense structure. This effectively improves the structural stability of the first carbon-based material, minimizes the penetration of electrolyte into the pore structure inside the particles, and thus effectively enhances the cycle performance of the secondary battery. Of course, this application does not intend to limit the area of all pore structures in the outer region of the first carbon-based material to less than or equal to 0.15 μm. 2 For example, more than 95%, and optionally more than 99%, of the pore structures can be controlled to have an area of less than or equal to 0.15 μm. 2 .
[0129] In some embodiments, the internal region of the first carbon-based material includes one or more particles with an area greater than or equal to 0.15 μm. 2 The pore structure may optionally include one or more pores with an area of 0.15 μm. 2 -2.0μm 2 The inventors further discovered that by including the aforementioned pore structure in the internal region of the first carbon-based material, on the one hand, the rolling pressure of the negative electrode sheet can be effectively reduced, particle damage can be effectively reduced, and sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, thereby reducing the risk of breakage of the first carbon-based material particles. On the other hand, the compaction density of the negative electrode film can be increased, and the volume change of the negative electrode film can be buffered.
[0130] The inventors further discovered that when the first carbon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as improving at least one of the energy density, kinetic performance, and cycle performance of the secondary battery.
[0131] In some embodiments, the specific surface area of the first carbon-based material is 0.7 m². 2 / g-1.8m 2 / g, optional 0.8m 2 / g-1.6m 2 / g. The first carbon-based material has a lower specific surface area, which can reduce the consumption of active ions during SEI film formation and improve the initial coulombic efficiency and cycle performance of the secondary battery.
[0132] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and optionally 10.0 μm-20.0 μm.
[0133] In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-35.0 μm, and optionally 17.0 μm-32.0 μm.
[0134] When the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. It can also reduce the specific surface area of the first carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery. In addition, it can form a reasonable pore structure with the second carbon-based material in the negative electrode film, improving the wetting and retention characteristics of the negative electrode film to the electrolyte.
[0135] In some embodiments, the (Dv90-Dv10) / Dv50 ratio of the first carbon-based material is ≤1.50, and can be selected as 0.7-1.40. When the (Dv90-Dv10) / Dv50 ratio of the first carbon-based material is within the above range, its particle packing performance is better, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure with the second carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and improve the cycle performance and kinetic performance of the secondary battery.
[0136] In some embodiments, the compacted density of the first carbon-based material powder under a pressure of 20,000 N is 1.75 g / cm³. 3 - 1.95g / cm 3 1.80g / cm³ is an optional value. 3-1.90g / cm 3 When the compaction density of the first carbon-based material powder is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the first carbon-based material in the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0137] In some embodiments, the tap density of the first carbon-based material is 0.80 g / cm³. 3 -1.50g / cm 3 0.85g / cm³ is an optional value. 3 -1.45g / cm 3 When the tap density of the first carbon-based material is within the above-mentioned range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial to form a reasonable pore structure with the second carbon-based material of the negative electrode film, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0138] In some embodiments, the graphitization degree of the first carbon-based material is ≥93.5%, optionally 93.8%-98%, 94.5%-98%, or 95.0%-98%. When the graphitization degree of the first carbon-based material is within the above range, its specific capacity is higher, which is beneficial to improving the energy density of the secondary battery.
[0139] In some embodiments, the powder OI value of the first carbon-based material is 8-18, optionally 8-16. When the powder OI value of the first carbon-based material is within the above range, it is beneficial for receiving active ions and also beneficial for reducing the thickness expansion rate of the negative electrode film.
[0140] In some embodiments, the specific capacity of the first carbon-based material is ≥354 mAh / g, optionally between 354 mAh / g and 370 mAh / g. When the specific capacity of the first carbon-based material is within the above range, the energy density of the secondary battery can be improved.
[0141] In some embodiments, two diffraction peaks exist in the peak-separated pattern of the X-ray diffraction pattern of the first carbon-based material within the 2θ range of 25.5°-27.5°. When two diffraction peaks exist in the peak-separated pattern of the X-ray diffraction pattern of the first carbon-based material within the 2θ range of 25.5°-27.5°, the first carbon-based material may simultaneously contain a crystalline carbon component with a high degree of graphitization (e.g., crystalline carbon with a graphitization degree ≥95.0%) and a crystalline carbon component with a low degree of graphitization (e.g., crystalline carbon with a graphitization degree of 70%-90%). The crystalline carbon component with a low degree of graphitization can have a larger interlayer spacing, which is beneficial for the diffusion of active ions and thus can improve the kinetic performance of the secondary battery; the crystalline carbon component with a high degree of graphitization can give the first carbon-based material a high specific capacity and / or compaction density, thereby improving the energy density of the secondary battery. Therefore, when the X-ray diffraction pattern of the first carbon-based material has two diffraction peaks in the range of 2θ of 25.5°-27.5°, it is beneficial to improve the energy density and kinetic performance of the secondary battery.
[0142] In some embodiments, of the two diffraction peaks, the one with the smaller 2θ is designated as the first peak, and the one with the larger 2θ is designated as the second peak. The ratio of the peak intensity of the first peak to the peak intensity of the second peak is 10:90-40:60, optionally 15:85-35:65 or 15:85-30:70. Further research by the inventors revealed that when the ratio of the peak intensity of the first peak to the peak intensity of the second peak is within the above range, it is beneficial for the secondary battery to better balance high energy density and good kinetic performance.
[0143] The peak-separated X-ray diffraction pattern of the first carbon-based material was obtained using Topas software and the Rietveld full-spectrum fitting refinement method. The 2θ peaks corresponded to the carbon 002 crystal plane at 25.5°–27.5°. The X-ray diffraction pattern of the first carbon-based material can be tested using an X-ray diffractometer, following JIS K 0131-1996 and JB / T 4220-2011. A Bruker D8 Discover X-ray diffractometer can be used. The testing conditions are as follows: the first carbon-based material is prepared using the flat plate method, with a copper target as the anode, CuKα rays as the radiation source, a voltage of 40 kV, a current of 40 mA, a 1 mm anti-scattering slit, a 2θ angle range of 20°–80°, a step size of 0.01671°, a step duration of 0.24 s, and a scan rate of 4° / min. In the peak-separated pattern of the X-ray diffraction pattern of the first carbon-based material of this application, the 2θ of the first peak is located between 26.256° and 26.456°, and the 2θ of the second peak is located between 26.509° and 26.569°.
[0144] In this application, the ratio of the peak intensity of the first peak to the peak intensity of the second peak is the ratio of the integral area of the first peak to the integral area of the second peak.
[0145] In some embodiments, the mass percentage of the first carbon-based material in the first active material is ≥20wt%, optionally 30wt%-70wt%. When the mass percentage of the first carbon-based material is within the above range, it is beneficial for the secondary battery to achieve both high energy density and good kinetic performance.
[0146] The second region 1022 includes a second active material, which includes a third carbon-based material.
[0147] In some embodiments, the surface of the third carbon-based material has a carbon coating layer. In some embodiments, more than 80% of the surface of the third carbon-based material is covered with a carbon coating layer; optionally, 90%-100% of the surface of the third carbon-based material is covered with a carbon coating layer. The third carbon-based material is located in the second region of the negative electrode film layer. When its surface has a carbon coating layer, it is beneficial to increase the rate of active ion insertion into the negative electrode film layer and improve the kinetic performance of the secondary battery.
[0148] In some embodiments, the carbon in the coating layer comprises amorphous carbon, which is beneficial for improving the kinetic performance of the secondary battery. The carbon may be formed by carbonization of an organic carbon source. The organic carbon source may be a carbon-containing material known in the art suitable for coating, such as one or more of coal tar pitch, petroleum pitch, phenolic resin, coconut shell, etc.
[0149] In some embodiments, the third carbon-based material comprises graphite having a carbon coating on its surface. Optionally, the graphite comprises at least one of synthetic graphite and natural graphite.
[0150] In some embodiments, the third carbon-based material comprises artificial graphite with a carbon coating layer on its surface, and the artificial graphite comprises secondary particles. Optionally, the proportion of secondary particles in the artificial graphite is ≥50%, for example, it can be 50%-100%, 60%-95%, 60%-100%, 65%-85%, 70%-100%, 75%-90%, 75%-85%, 80%-100%, 80%-90%, 85%-95%, or 90%-100%. When the third carbon-based material contains an appropriate proportion of secondary particles, it can increase the active ion channels in the negative electrode film layer and shorten the active ion insertion path, thereby further improving the kinetic performance of the secondary battery, and also reducing battery polarization and the occurrence of side reactions, thus enabling the secondary battery to achieve good cycle performance.
[0151] In this application, the proportion of secondary particles in artificial graphite refers to: taking a test sample randomly in the negative electrode film layer, taking multiple test areas randomly in the test sample, acquiring images of multiple test areas using a scanning electron microscope, and statistically analyzing the proportion of artificial graphite secondary particles in the second region of the negative electrode film layer in each image to the total number of artificial graphite particles in the second region. The average of multiple statistical results is the proportion of secondary particles in artificial graphite.
[0152] In some embodiments, the interlayer spacing of the 002 crystal plane of the second carbon-based material is smaller than that of the 002 crystal plane of the third carbon-based material. The larger interlayer spacing of the third carbon-based material is beneficial for the rapid insertion and extraction of active ions. Therefore, by adjusting the interlayer spacing of the 002 crystal plane of the second carbon-based material to be smaller than that of the 002 crystal plane of the third carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0153] In some embodiments, the degree of graphitization of the second carbon-based material is greater than that of the third carbon-based material. The third carbon-based material has a lower degree of graphitization and a larger interlayer spacing, which is beneficial for the rapid insertion and extraction of active ions. Therefore, by adjusting the degree of graphitization of the second carbon-based material to be greater than that of the third carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0154] In some embodiments, the specific capacity of the second carbon-based material is greater than that of the third carbon-based material. The third carbon-based material has a smaller specific capacity and a larger interlayer spacing, which is conducive to the rapid insertion and extraction of active ions, thereby further improving the kinetic performance of the secondary battery; the second carbon-based material and the first carbon-based material have higher specific capacities, which is also conducive to the secondary battery achieving both high energy density and good kinetic performance.
[0155] In some embodiments, the powder compaction density of the second carbon-based material at 20,000 N pressure is greater than that of the third carbon-based material at 20,000 N pressure. By adjusting the powder compaction density of the second carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0156] In some embodiments, the powder compaction density of the first carbon-based material at 20,000 N pressure is greater than that of the third carbon-based material at 20,000 N pressure. By adjusting the powder compaction density of the first carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0157] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is greater than that of the third carbon-based material. By adjusting the volume distribution particle size Dv50 of the second carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0158] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is greater than that of the third carbon-based material. By adjusting the volume distribution particle size Dv50 of the first carbon-based material to be greater than that of the third carbon-based material, it is beneficial to have a reasonable pore distribution in the thickness direction of the negative electrode film, thereby improving the transport performance of active ions and electrons, enhancing the wetting and retention characteristics of the negative electrode film in the electrolyte, reducing the volume change of the negative electrode film, and thus improving the cycle performance, safety performance, and kinetic performance of the secondary battery.
[0159] The inventors further discovered that when the third carbon-based material, in addition to satisfying the above design, further satisfies one or more of the following conditions, it can further improve the performance of the secondary battery, such as improving at least one of the energy density, kinetic performance, and cycle performance of the secondary battery.
[0160] In some embodiments, the volumetric particle size Dv50 of the third carbon-based material is 10.0 μm-22.0 μm, optionally 11.5 μm-20.0 μm. When the volumetric particle size Dv50 of the third carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. Additionally, it can reduce the specific surface area of the third carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery.
[0161] In some embodiments, the (Dv90-Dv10) / Dv50 ratio of the third carbon-based material is ≤1.65, and can be selected as 0.90-1.65. When the (Dv90-Dv10) / Dv50 ratio of the third carbon-based material is within the above range, its particle packing performance is better, which is beneficial to improving the compaction density of the negative electrode film, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial for the negative electrode film to have a suitable pore distribution, improving the wetting and retention characteristics of the negative electrode film to the electrolyte, and improving the cycle performance and kinetic performance of the secondary battery.
[0162] In some embodiments, the OI value of the third carbon-based material powder is 2.0-6.5, preferably 2.0-6.0. The lower OI value of the third carbon-based material powder indicates that the particles have active ion insertion ports in all directions, enabling rapid reception of active ions from the positive electrode, thereby further improving the kinetic performance of the secondary battery. Furthermore, the high isotropy of the third carbon-based material particles facilitates the dispersion of the expansion rate during active ion insertion, reducing the expansion rate of the negative electrode film thickness, and further improving the cycle performance of the secondary battery.
[0163] In some embodiments, the compacted density of the third carbon-based material at a pressure of 20,000 N is 1.65 g / cm³. 3 -2.00g / cm 3 The option is 1.68g / cm³. 3 -1.98g / cm 3 When the compaction density of the third carbon-based material powder is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery; it is also beneficial to have a suitable pore distribution, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film to the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0164] In some embodiments, the tap density of the third carbon-based material is 0.85 g / cm³. 3 -1.25g / cm 3 0.90 g / cm³ is an option. 3 -1.25g / cm 3 When the tap density of the third carbon-based material is within the above range, it can increase the compaction density of the negative electrode film and improve the energy density of the secondary battery. It is also beneficial for the negative electrode film to have a suitable pore distribution, improve the active ion and electron transport performance, improve the wetting and retention characteristics of the negative electrode film in the electrolyte, and thus improve the cycle performance and kinetic performance of the secondary battery.
[0165] In some embodiments, the graphitization degree of the third carbon-based material is ≤96%, optionally 90.5%-95.5%. When the graphitization degree of the third carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film, thereby helping the secondary battery to achieve both high energy density and good kinetic performance.
[0166] In some embodiments, the specific surface area of the third carbon-based material is 0.9 m². 2 / g-2.5m 2 / g, can be selected as 0.95m 2 / g-2.45m 2 / g. When the specific surface area of the third carbon-based material is within the above range, it is beneficial for the rapid insertion and extraction of active ions, improves the kinetic performance of the secondary battery, and can also reduce the consumption of active ions by the SEI film formation, thereby improving the first coulombic efficiency of the secondary battery.
[0167] In some embodiments, the specific capacity of the third carbon-based material is 340 mAh / g-360 mAh / g, optionally 345 mAh / g-360 mAh / g. Having a specific capacity within this range allows the third carbon-based material to possess good active ion transport performance, improving the kinetic performance of the secondary battery, while also helping the secondary battery achieve a relatively high energy density.
[0168] like Figures 1 to 3 As shown, the negative electrode film layer 102 also includes an intermediate region 1023 located between the first region 1021 and the second region 1022 of the negative electrode film layer, with a thickness of 0.4H (H represents the thickness of the negative electrode film layer 102).
[0169] In some embodiments, the intermediate region includes the first active material and / or the second active material. For example, such as... Figure 2 As shown, the intermediate region 1023 can be composed of the same material as the first region 1021. Therefore, the distribution area of the first active material in the thickness direction of the negative electrode film 102 is within a thickness range from the second surface 102b of the negative electrode film to 0.7H; or, as... Figure 3 As shown, the intermediate region 1023 can be composed of the same material as the second region 1022. Therefore, the distribution area of the second active material in the thickness direction of the negative electrode film 102 is within a thickness range from the first surface 102a of the negative electrode film to 0.7H; or, as shown... Figure 1 As shown, the intermediate region 1023 includes both a first active material and a second active material. In this case, the intermediate region 1023 includes both a layer structure having the first active material and a layer structure having the second active material. The two layer structures may also have a layer interface.
[0170] In some embodiments, the first region of the negative electrode film may further include other negative electrode active materials known in the art besides the first and second carbon-based materials described above. For example, it may also include silicon-based materials. Silicon-based materials can improve the pore structure in the negative electrode film, facilitating electrolyte wetting and retention, and improving the kinetic performance of the secondary battery; at the same time, they can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery. Optionally, the silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials.
[0171] In some embodiments, when the first region of the negative electrode film further includes a silicon-based material, the mass percentage of the silicon-based material in the first region of the negative electrode film can be ≤10%, for example, it can be 1%-8%, 2%-6%, or 3%-7%. This allows the secondary battery to achieve good cycle performance while improving its kinetic performance and energy density.
[0172] In some embodiments, the second region of the negative electrode film may further include other negative electrode active materials known in the art besides the aforementioned third carbon-based material. For example, it may also include silicon-based materials. Silicon-based materials can improve the pore structure in the negative electrode film, facilitating electrolyte wetting and retention, and improving the kinetic performance of the secondary battery; at the same time, they can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery. Optionally, the silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials.
[0173] In some embodiments, when the second region of the negative electrode film further includes a silicon-based material, the mass percentage of the silicon-based material in the second region of the negative electrode film can be ≤10%, for example, 1%-8%, 2%-6%, or 3%-7%. This allows the secondary battery to achieve good cycle performance while improving its kinetic performance and energy density.
[0174] In some embodiments, both the first region and the second region comprise silicon-based materials, and the mass percentage of the silicon-based material in the first region is less than or equal to the mass percentage of the silicon-based material in the second region. During the charging and discharging process of the secondary battery, the volume expansion of silicon-based materials is greater than that of carbon-based materials. This is beneficial for the second region of the negative electrode film to have higher porosity, thereby improving the wetting characteristics of the negative electrode film to the electrolyte, enhancing the transport performance of active ions, and improving the cycle performance and / or kinetic performance of the secondary battery. Furthermore, the higher porosity of the second region of the negative electrode film can also improve the active ion transport performance of the first region of the negative electrode film.
[0175] In some embodiments, the intermediate region of the negative electrode film further includes a silicon-based material.
[0176] In some embodiments, the first region, the second region, and the intermediate region of the negative electrode film may optionally include a negative electrode conductive agent and / or a negative electrode binder.
[0177] This application does not impose any particular limitation on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0178] This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0179] In some embodiments, the first region, the second region, and the intermediate region of the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.
[0180] In some embodiments, the porosity of the negative electrode film is 18.0%-36.7%, optionally 19.0%-34.0%. This is beneficial for the negative electrode film to achieve both high capacity and a reasonable pore structure, which in turn is beneficial for the secondary battery to achieve both high energy density and good cycle performance and kinetic performance.
[0181] In some embodiments, the compaction density of the negative electrode film is 1.50 g / cm³. 3 -1.85g / cm 3 1.55g / cm³ is an optional value. 3 -1.80g / cm 3 This allows the negative electrode film to achieve both high capacity and good active ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and kinetic performance.
[0182] In some embodiments, the areal density of the negative electrode film is 5.0 mg / cm³. 2 -25.0mg / cm 2 The option is 5.5 mg / cm³. 2 -22.5mg / cm 2This allows the negative electrode film to achieve both high capacity and good active ion and electron transport performance, which in turn helps the secondary battery to achieve both high energy density and good cycle performance and kinetic performance.
[0183] In some embodiments, the OI value of the negative electrode film is ≤40.0, and can be selected as 5.0-40.0. This is beneficial for improving the active ion intercalation performance of the negative electrode film and also allows the negative electrode film to have a low thickness expansion rate, which in turn helps the secondary battery to achieve both good cycle performance and kinetic performance.
[0184] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0185] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode film layer.
[0186] The negative electrode current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of these opposing surfaces. It should be noted that the negative electrode film layer parameters (e.g., compacted density, areal density, porosity, OI value, thickness, etc.) given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. When the negative electrode film layer is disposed on both sides of the negative electrode current collector, if the parameters of the negative electrode film layer on either side satisfy those of this application, it is considered to fall within the protection scope of this application.
[0187] In this application, the presence of a carbon coating layer on the surface of a material (e.g., a first carbon-based material, a second carbon-based material, a third carbon-based material, etc.) can be determined by transmission electron microscopy.
[0188] In this application, the specific surface area of materials (e.g., first carbon-based material, second carbon-based material, third carbon-based material, etc.) has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be tested using the nitrogen adsorption specific surface area analysis method according to GB / T19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.
[0189] In this application, the degree of graphitization of materials (e.g., first carbon-based materials, second carbon-based materials, third carbon-based materials, etc.) has a meaning known in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as a Bruker D8 Discover) can be used for testing, and the testing can be performed with reference to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material's crystal structure. 002 Then, according to the formula g = (0.344 - d) 002 The degree of graphitization is calculated as d / (0.344-0.3354)×100%. In the above formula, d... 002 It is the average interlayer spacing of the C(002) crystal plane in the material crystal structure, expressed in nanometers (nm).
[0190] In this application, the volumetric particle sizes Dv10, Dv50, and Dv90 of the materials (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) have meanings known in the art, representing the particle sizes corresponding to a cumulative volumetric distribution percentage of 10%, 50%, and 90%, respectively, and can be determined using instruments and methods known in the art. For example, they can be determined using a laser particle size analyzer, referring to GB / T 19077-2016. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0191] In this application, the powder compaction density of materials (e.g., first carbon-based material, second carbon-based material, third carbon-based material, etc.) has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be determined by referring to GB / T 24533-2009 using an electronic pressure testing machine (e.g., a UTM7305 type electronic pressure testing machine). An exemplary test method is as follows: Weigh 1g of sample powder and add it to a container with a bottom area of 1.327cm². 2 In the mold, the pressure is increased to 2000 kg, held for 30 s, then the pressure is released and held for 10 s. The compaction density of the material under 20000 N pressure is then recorded and calculated.
[0192] In this application, the tap density of materials (e.g., first carbon-based material, second carbon-based material, third carbon-based material, etc.) has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be determined using a powder tap density tester according to GB / T5162-2006. The testing instrument can be Dandong Baite BT-301, with the following testing parameters: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, number of vibrations 5000 times, and graduated cylinder 25mL.
[0193] In this application, the OI value of the powder material (e.g., first carbon-based material, third carbon-based material, etc.) has a meaning known in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as a Bruker D8 Discover) can be used for testing, and the testing can be performed with reference to JIS K 0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction pattern of the powder sample. Based on the formula OI value = I... 004 / I 110 The OI value of the powder in the sample was calculated. 004 I is the integrated area of the diffraction peak of the crystalline carbon 004 crystal plane in the powder sample. 110 This represents the integrated area of the diffraction peak on the 110 crystal plane of crystalline carbon in the powder sample. In the X-ray diffraction analysis of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the ray wavelength... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min.
[0194] In this application, primary particles and secondary particles have meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to aggregated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished using scanning electron microscopy (SEM) images.
[0195] In this application, the specific capacity of materials (e.g., first carbon-based material, second carbon-based material, third carbon-based material, etc.) has a meaning known in the art and can be tested using methods known in the art. An exemplary testing method is as follows: Sample powder is mixed uniformly with conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) at a mass ratio of 91.6:1.8:6.6 and solvent N-methylpyrrolidone (NMP) to prepare a slurry; the prepared slurry is coated onto the surface of the negative electrode current collector copper foil and dried in an oven for later use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a solution with a concentration of 1 mol / L. The electrolyte was prepared; then, using a lithium metal sheet as the counter electrode and a polyethylene (PE) film as the separator, the CR2430 coin cell was assembled with the electrolyte in an argon-protected glove box. After the coin cell was left to stand for 12 hours, it was discharged at 25°C with a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged again with a constant current of 50μA to 0.005V. After standing for 10 minutes, it was discharged again with a constant current of 10μA to 0.005V. Then, it was charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the sample mass is the specific capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.).
[0196] In this application, the areal density of the negative electrode film has a meaning known in the art and can be tested using methods known in the art. For example, a negative electrode sheet coated on one side and cold-pressed (if it is a double-sided coated negative electrode sheet, the negative electrode film layer on one side can be wiped off first) can be cut into small circular pieces with an area of S1, weighed, and recorded as M1. Then, the negative electrode film layer of the weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector is weighed and recorded as M0. The areal density of the negative electrode sheet = (M1-M0) / S1.
[0197] In this application, the compaction density of the negative electrode film layer has a meaning known in the art and can be tested using methods known in the art. The compaction density of the negative electrode film layer = the areal density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer has a meaning known in the art and can be tested using methods known in the art, such as using a micrometer (e.g., a Mitutoyo 293-100 model with an accuracy of 0.1 μm).
[0198] In this application, the porosity of the negative electrode film layer has a meaning known in the art and can be determined using methods known in the art. An exemplary test method is as follows: Take a negative electrode sheet coated on one side and cold-pressed (if it is a double-sided coated negative electrode sheet, the negative electrode film layer on one side can be wiped off first), cut it into small circular samples of a certain area, and calculate the apparent volume V1 of the negative electrode sheet; referring to GB / T24586-2009, using an inert gas (such as helium or nitrogen) as the medium, employ the gas displacement method and use a true density meter to measure the true volume V2 of the negative electrode sheet. The porosity of the negative electrode film layer = (V1-V2) / V1×100%. Multiple negative electrode sheet samples (e.g., 30 sheets) with good appearance and no powder shedding at the edges can be tested, and the average value of the results is taken, thereby improving the accuracy of the test results. The testing instrument can be a Micromeritics AccuPyc II 1340 true density meter.
[0199] In this application, the OI value of the negative electrode film has a meaning known in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as a Bruker D8 Discover) can be used for testing, and the testing can be performed with reference to JIS K 0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction pattern of the negative electrode sheet. Based on the formula OI value = I... 004 / I 110 The OI value of the negative electrode film was calculated. 004 I is the integrated area of the diffraction peaks of the crystalline carbon 004 crystal plane in the negative electrode film. 110 This represents the integrated area of the diffraction peak on the 110 crystal plane of crystalline carbon in the negative electrode film. In the X-ray diffraction analysis of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the ray wavelength... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min.
[0200] It should be noted that the above-mentioned tests on various parameters of the first active material, the second active material, or the negative electrode film can be performed by sampling and testing from the prepared secondary battery according to the following steps.
[0201] The secondary battery is discharged (for safety, it is generally left fully discharged); after disassembling the secondary battery, the negative electrode is removed and soaked in dimethyl carbonate for a certain period of time (e.g., 2-10 hours); then the negative electrode is removed and dried at a certain temperature and time (e.g., 60°C for more than 4 hours), and then the negative electrode is removed. At this point, samples can be taken from the dried negative electrode to test the parameters related to the negative electrode film, such as the areal density, compaction density, porosity, and OI value of the negative electrode film.
[0202] The dried negative electrode sheet is baked at a certain temperature and time (e.g., 400℃ for more than 2 hours). Select a region in the baked negative electrode sheet and take a sample of the second active material (a blade can be used to scrape the powder for sampling). The sampling location is the second region of the negative electrode film. Then, take a sample of the first active material in the same way. The sampling location is the first region of the negative electrode film. The collected first and second active materials are sieved (e.g., sieved through a 200-mesh sieve) to finally obtain the first and second active material samples that can be used to test the material parameters of the present application.
[0203] [Preparation method of negative electrode sheet]
[0204] This application also provides a method for preparing the negative electrode sheet of this application. The method includes the following steps: providing a first slurry containing a first active material and a second slurry containing a second active material; coating the first slurry onto a negative current collector, coating the second slurry onto the first slurry, and obtaining the negative electrode sheet after drying and cold pressing.
[0205] In some embodiments, the first active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a first slurry.
[0206] In some embodiments, the second active material, along with optional conductive agents, optional binders, and other optional additives, can be dispersed in a solvent (e.g., deionized water) to form a second slurry.
[0207] In some embodiments, the first active material comprises a mixture of a first carbon-based material and a second carbon-based material.
[0208] In some embodiments, the second active material comprises a third carbon-based material.
[0209] In some embodiments, the first slurry and / or the second slurry further include a silicon-based material.
[0210] The first and second slurries can be coated simultaneously in one step or in two separate steps. In some embodiments, the first and second slurries are coated simultaneously in one step. Simultaneous coating in one step can reduce the negative electrode film resistance, thereby further improving the kinetic and cycle performance of the secondary battery.
[0211] The coating weights of the first and second slurries can be adjusted according to actual conditions.
[0212] In this application, the first active material, the second active material, etc. mentioned above can be obtained commercially or prepared by the method described in this application.
[0213] In some embodiments, the preparation method of the first carbon-based material includes: step 1, providing a raw material having a plurality of pore structures; step 2, mixing the raw material and a filler material uniformly according to a predetermined ratio, then holding the mixture at a first temperature T1 for a first time t1, and then cooling it to room temperature to obtain an intermediate; step 3, holding the obtained intermediate at a second temperature T2 for a second time t2, and then obtaining the first carbon-based material.
[0214] In some embodiments, in step 1, the raw material used to prepare the first carbon-based material includes natural graphite. Optionally, the natural graphite includes one or more of flake graphite, natural spherical graphite, and microcrystalline graphite, and more preferably includes natural spherical graphite.
[0215] "Natural spherical graphite" refers to natural graphite with a spherical or near-spherical shape, but not all natural graphite particles are controlled to be ideally spherical. In some embodiments, natural spherical graphite with the desired particle size and morphology can be obtained by pre-treating flake graphite. Optionally, the pre-treatment includes processes such as crushing, grading, spheroidizing, and purification.
[0216] In some embodiments, in step 1, the volume distribution particle size Dv50 of the raw material can be 7.0 μm-25.0 μm, and can be optionally 10.0 μm-20.0 μm, which is beneficial for preparing a first carbon-based material with the desired volume distribution particle size.
[0217] In some embodiments, in step 1, the specific surface area of the raw material may be ≥2.5m². 2 / g, optional 2.5m 2 / g-10.0m 2 / g. When the specific surface area of the raw material is within the above range, it is beneficial for subsequent filling processing and obtaining the first carbon-based material with the required specific surface area. It is also beneficial for the first carbon-based material to have both high capacity and high initial coulombic efficiency. In addition, it is beneficial for the first carbon-based material to have better kinetic performance.
[0218] In some embodiments, in step 2, the softening point temperature of the filler material is 102℃-175℃. Optionally, the softening point temperature of the filler material is 106℃-162℃, 106℃-156℃, 106℃-150℃, 106℃-146℃, 106℃-142℃, 110℃-162℃, 110℃-156℃, 110℃-150℃, 110℃-146℃, or 110℃-142℃.
[0219] In some embodiments, in step 2, the volume distribution particle size Dv50 of the filler material is less than or equal to 6 μm, and can be selected as 1 μm-6 μm, 1 μm-5 μm, 2 μm-5 μm, or 3 μm-5 μm. This is beneficial for the filler material to fill into the pore structure of the raw material after being heated and melted, and also helps to improve the dispersion uniformity of the filler material and the raw material.
[0220] In some embodiments, in step 2, the coking value of the filler material is 19%-47%, optionally 22%-40%. In this application, the coking value of the filler material has a meaning known in the art and can be measured using instruments and methods known in the art. For example, it can be measured with reference to GB / T 8727-2008.
[0221] In some embodiments, in step 2, the filler material includes one or more of coal tar pitch, petroleum pitch, polymer compounds, and resins, and may optionally include one or more of coal tar pitch and petroleum pitch.
[0222] In some embodiments, in step 2, the mass ratio of the filler material to the raw material is (10-40):100, optionally (10-30):100, (10-25):100, (10-20):100, (12-30):100, (12-20):100, (14-28):100, (15-25):100.
[0223] In step 2, by adjusting one or more parameters such as the type of filler material, softening point, coking value, and amount added to be within the above range, it is beneficial to adjust the number and / or size of pores in the outer and inner regions of the first carbon-based material to be within a suitable range, and to adjust the S2 / S1 ratio of the first carbon-based material to be within a suitable range.
[0224] By adjusting parameters such as the type of filler material, softening point, coking value, and amount added to be within the above range, the filler material has low viscosity after being heated and melted, maintaining good fluidity. At the same time, it is not easy to stick to the raw material particles, which can reduce the agglomeration of raw material particles in subsequent preparation processes. This can also reduce problems such as increased surface defects and increased surface active sites of the first carbon-based material particles due to the need to add a deagglomeration process.
[0225] In some embodiments, the heating process in step 2, which involves uniformly mixing the raw material and the filler material in a predetermined ratio and then heating them to a first temperature T1, is a staged heating process.
[0226] In some embodiments, the staged heating process includes a first heating process, a second heating process, and a third heating process.
[0227] In some embodiments, the first heating process involves heating to 200°C-250°C and holding at that temperature for 0.5h-3h.
[0228] In some embodiments, the second heating process involves heating to 450°C-550°C and holding at that temperature for 0h-2h. When the holding time is 0h, it indicates that when the temperature reaches the range of 450°C-550°C, no holding process is performed, but the temperature continues to rise to the first temperature T1.
[0229] In some embodiments, the third heating process involves heating to the first temperature T1 and holding at that temperature for a first time t1.
[0230] In the staged heating process, the temperature is first raised to 200℃-250℃. Since the heating temperature is higher than the softening point of the filler material, the filler material melts and softens upon heating. Holding at this temperature for 0.5h-3h allows it to flow and fill the pore structure of the raw material. Then, the temperature is raised to 450℃-550℃. At this point, the molten and softened filler material undergoes a carbonization reaction, gradually forming a semi-coke state, becoming a viscous liquid or solid, thereby preventing the filler material from entering all the pore structures of the raw material. Finally, the temperature is raised to the first temperature. At this point, the filler material undergoes a carbonization reaction, which allows the pore structure occupied by the filler material to be effectively filled.
[0231] In some embodiments, in step 2, the temperature is increased to the first temperature T1 at a rate of 1°C / min to 10°C / min. For example, the heating rate can be a range of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any of the above values. Optionally, the heating rate can be 1.5°C / min to 8°C / min, 1.5°C / min to 6°C / min, 2°C / min to 6°C / min, or 2°C / min to 5°C / min.
[0232] In some embodiments, the heating rate of the first heating process can be 1℃ / min-10℃ / min, and can be selected as 1.5℃ / min-8℃ / min, 1.5℃ / min-6℃ / min, 2℃ / min-6℃ / min, or 2℃ / min-5℃ / min.
[0233] In some embodiments, the heating rate of the second heating process can be 1℃ / min-10℃ / min, and can be selected as 2℃ / min-8℃ / min.
[0234] In some embodiments, the heating rate of the third heating process can be 1℃ / min-10℃ / min, and can be selected as 2℃ / min-8℃ / min.
[0235] In some embodiments, in step 2, the first temperature T1 is 700℃-1200℃. For example, the first temperature T1 can be a range of 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1200℃, or any value above. Optionally, the first temperature T1 is 750℃-1100℃, 800℃-1100℃, or 850℃-1000℃.
[0236] In some embodiments, in step 2, the first time t1 is 1h-5h. For example, the first time t1 can be a range of 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any of the above values. Optionally, the first time t1 is 2h-4h.
[0237] In some embodiments, in step 2, the heat treatment can be carried out in equipment capable of programmed temperature rise, such as an induction furnace, roller kiln, rotary kiln, pusher kiln, vertical granulation kettle, horizontal granulation kettle, vertical reactor, horizontal reactor, or drum furnace.
[0238] In some embodiments, in step 2, the heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.
[0239] In step 2, by adjusting one or more of the heating rate, first temperature, first time, heating process, etc., within the above range, it is beneficial to adjust the number and / or size of pores in the outer and inner regions of the first carbon-based material within a suitable range, and to adjust the S2 / S1 ratio of the first carbon-based material within a suitable range.
[0240] In some embodiments, in step 3, the second temperature T2 is 1960℃-2640℃. Optionally, the second temperature T2 is 2025℃-2525℃, 2025℃-2475℃, 2025℃-2425℃, 2025℃-2375℃, 2075℃-2525℃, 2075℃-2475℃, 2075℃-2425℃, or 2075℃-2375℃.
[0241] In some embodiments, in step 3, the second time t2 is 1.5h-6h. For example, the second time t1 can be a range of 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, or any of the above values. Optionally, the second time t2 is 2h-5h.
[0242] In some embodiments, in step 3, the heat treatment can be carried out in an intermediate frequency furnace, a box-type graphitization furnace, an Atchison graphitization furnace, a continuous graphitization furnace, or an internal series graphitization furnace.
[0243] In some embodiments, in step 3, the medium-frequency furnace and the continuous graphitization heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.
[0244] In step 3, by adjusting one or more of the second temperature and the second time within the above range, it is beneficial to adjust the content of disordered carbon in the first carbon-based material within a suitable range, and to ensure that the first carbon-based material has a suitable degree of graphitization, interlayer spacing, etc.
[0245] In the above-mentioned method for preparing the first carbon-based material, by adjusting one or more of the parameters of natural graphite, the parameters of the filler material, the heating rate, the first temperature, the first time, the heating process, the second temperature, and the second time within the above-mentioned range, it is beneficial to adjust the parameters of the first carbon-based material such as S2 / S1, degree of graphitization, interlayer spacing, specific capacity, specific surface area, particle size, powder compaction density, tap density, and powder OI value.
[0246] [Positive electrode plate]
[0247] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0248] The positive electrode current collector can be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil can be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0249] The positive electrode film layer usually comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is usually formed by coating a positive electrode slurry on the positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring the mixture uniformly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0250] The positive electrode active material may employ a positive electrode active material for secondary batteries well known in the art.
[0251] When the secondary battery of the present application is a lithium ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates and respective modified compounds thereof. Examples of the lithium transition metal oxide may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and respective modified compounds thereof. Examples of the lithium-containing phosphate may include, but are not limited to, one or more of lithium iron phosphate, composite material of lithium iron phosphate and carbon, lithium manganese phosphate, composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, composite material of lithium manganese iron phosphate and carbon, and respective modified compounds thereof.
[0252] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and one or more of modified compounds thereof, wherein 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.
[0253] In some embodiments, as an example, the positive electrode active material for lithium-ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 and LiMnPO4.
[0254] In this application, the modified compounds of the above-mentioned positive electrode active materials may be those that have undergone doping modification and / or surface coating modification of the positive electrode active materials.
[0255] [Electrolytes]
[0256] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0257] The type of electrolyte salt is not specifically limited and can be selected according to actual needs.
[0258] When the secondary battery of this application is a lithium-ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0259] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0260] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain performance characteristics of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high-temperature performance of the secondary battery, and additives that improve the low-temperature power performance of the secondary battery.
[0261] [Isolation membrane]
[0262] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0263] In some embodiments, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.
[0264] In some embodiments, the positive electrode, the separator, and the negative electrode can be fabricated into an electrode assembly using a winding process or a stacking process.
[0265] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0266] In some embodiments, the outer packaging may be a hard shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging may also be a flexible package, such as a pouch. The material of the flexible package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0267] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 5 This is an example of a square-structured secondary battery 5.
[0268] In some embodiments, such as Figure 6 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.
[0269] The method for preparing the secondary battery described in this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding or stacking process. The electrode assembly is then placed in an outer packaging, dried, and injected with an electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.
[0270] In some embodiments of this application, the secondary battery according to this application can be assembled into a battery module. The number of secondary batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0271] Figure 7 This is a schematic diagram of battery module 4 as an example. Figure 7 As shown, in battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0272] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0273] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0274] Figure 8 and Figure 9 This is a schematic diagram of battery pack 1 as an example. Figure 8 and Figure 9As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0275] This application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack described in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may be, but is not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0276] The electrical device can be equipped with a secondary battery, battery module, or battery pack according to its usage requirements.
[0277] Figure 10 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0278] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.
[0279] Example
[0280] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0281] In the following embodiments and comparative examples, the first carbon-based material used can be prepared by the method described in this application.
[0282] (I) Preparation of the first carbon-based material:
[0283] Flake graphite is mechanically crushed, graded, spheroidized, and purified to obtain natural spherical graphite. The obtained natural spherical graphite is mixed with petroleum asphalt, and then the mixture is placed in a programmable temperature-controlled device for staged heat treatment. After the treatment, it is cooled to room temperature to obtain an intermediate. The obtained intermediate is placed in a graphitization furnace for heat treatment, and after demagnetization and sieving, a first carbon-based material is obtained. In the above process, the preparation process of the first carbon-based material described above can be controlled to ensure that the Dv50, interlayer spacing, and S2 / S1 of the first carbon-based material are within the ranges in Table 1.
[0284] The S2 / S1 ratio of the first carbon-based material was obtained by the following method: The first carbon-based material powder was mixed evenly with a sample binder and then coated onto copper foil. It was dried at 60°C for 30 minutes. The sample was cut into 6mm × 6mm pieces and pasted onto the sample stage of a CP-type argon ion cross-section polisher. The sample was then cut using a plasma beam to obtain the cross-section of the first carbon-based material, with the cross-section passing through the center of the first carbon-based material particle. The testing instrument could be an IB-09010CP argon ion cross-section polisher from JEOL Corporation, Japan. The cross-section of the first carbon-based material was scanned using a scanning electron microscope. The test can be performed according to JY / T010-1996. The testing instrument could be a Sigma 300 scanning electron microscope from ZEISS Corporation, Germany. The region extending 0.25L from the surface of the first carbon-based material particle into the particle's interior is designated as the outer region, and the region inside the outer region is designated as the inner region. L represents the minor axis length of the first carbon-based material particle. The total pore area S1 of the outer region of the first carbon-based material and the total pore area S2 of the inner region of the first carbon-based material are calculated using image processing software. The image processing software can be AVIZO.
[0285] In the following embodiments and comparative examples, the second carbon-based material and the third carbon-based material can be commercially available.
[0286] The secondary batteries in Examples 1-25 were all prepared according to the following method.
[0287] A mixture of the first active material (a first carbon-based material and a second carbon-based material, see Table 1, mass ratio 50:50), conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 96.4:1:1.2:1.4 to form a first slurry. A second active material (a third carbon-based material, see Table 1), conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were also thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 96.4:1:1.2:1.4 to form a second slurry. The first and second slurries were simultaneously extruded using a dual-cavity coating device. The first slurry was coated onto the negative electrode current collector copper foil, and the second slurry was coated onto the first slurry. After drying and cold pressing, the negative electrode sheet was obtained. The coating weights of the first and second slurries were the same. The compaction density of the negative electrode film was 1.72 g / cm³. 3 -1.76g / cm 3 .
[0288] Lithium iron phosphate, conductive agent carbon black (Super P), and binder polyvinylidene fluoride were mixed in a weight ratio of 96:2:2, and an appropriate amount of solvent NMP was added. The mixture was stirred until homogeneous to obtain a positive electrode slurry. The positive electrode slurry was coated onto both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0289] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 was then dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0290] A polyethylene film is used as a separator and is placed in sequence with the positive and negative electrode sheets prepared above, so that the separator is placed between the positive and negative electrode sheets to play a separating role. Then, the electrode assembly is wound to obtain the electrode assembly. The electrode assembly is placed in the outer packaging, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, shaping and other processes, a secondary battery is obtained.
[0291] Comparative Example 1
[0292] The preparation method of the secondary battery in Comparative Example 1 is similar to that in Examples 1-25, except for the preparation of the negative electrode sheet.
[0293] The third carbon-based material shown in Table 1, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were thoroughly mixed in a weight ratio of 96.4:1:1.2:1.4 with an appropriate amount of deionized water to form a slurry. The slurry was coated onto the negative electrode current collector copper foil, and after drying and cold pressing, the negative electrode sheet was obtained. The compaction density of the negative electrode film was 1.72 g / cm³. 3 -1.76g / cm 3 .
[0294] Performance testing
[0295] (1) Fast charging performance test of secondary batteries
[0296] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to 0.05C at a constant voltage. After standing for 5 minutes, the secondary battery was discharged to 2.5V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0297] Then, the secondary battery was sequentially charged at constant current rates of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, and 3.0C0 until it reached 3.65V or 0V negative terminal cutoff potential (whichever comes first). After each charge, it was discharged to 2.5V at 1C0. The state of charge (SOC) was recorded at different charging rates until it reached 10%, 20%, 30%, ..., 80%. By plotting the negative electrode potential corresponding to the state of charge (SOC), the charging rate-negative electrode potential curves under different SOC states are obtained. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. This charging rate is the charging window under that SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC, respectively. The charging time T (assuming no lithium plating in the secondary battery) from 10%SOC to 80%SOC is calculated according to the formula (60 / C20%SOC+60 / C30%SOC +60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, in minutes. The shorter the charging time, the better the kinetic performance of the secondary battery.
[0298] (2) Cycle performance test of secondary batteries
[0299] At 45℃, the secondary battery was charged at a constant current of 1C to 3.65V, then charged at a constant voltage to a current of 0.05C. After resting for 5 minutes, the secondary battery was discharged at a constant current of 1C to 2.5V. The discharge capacity at this point was recorded, which is the initial discharge capacity. The secondary battery was subjected to a cyclic charge-discharge test using the above method, and the discharge capacity after each cycle was recorded until the discharge capacity of the secondary battery after cycles decreased to 80% of the initial discharge capacity. The test was then stopped, and the number of cycles of the secondary battery was recorded.
[0300] (3) Thickness expansion rate test of negative electrode film
[0301] At 25℃, the secondary battery was charged at a constant current of 0.33C to 3.65V, then charged at a constant voltage to a current of 0.05C. After standing for 10 minutes, the negative electrode sheet at 100% SOC was taken, and the average thickness of the negative electrode film was measured and recorded as D1. The thickness expansion rate of the negative electrode film = (D1-D0) / D0. D0 represents the average thickness of the negative electrode film after cold pressing.
[0302] The negative electrode film layer of Comparative Example 1 only includes the third carbon-based material, and the powder compaction density of the third carbon-based material is relatively low. Therefore, by increasing the compaction density of the negative electrode film layer (the compaction density of the negative electrode film layer in Comparative Example 1 is 1.72 g / cm³), the negative electrode film layer can be improved. 3 -1.76g / cm 3 Increasing the energy density of a battery leads to a deterioration in both cycle performance and kinetic performance, while also resulting in a higher thickness expansion rate of the negative electrode film. Furthermore, due to the low specific capacity of the third carbon-based material, increasing the compaction density of the negative electrode film has limited effect on improving the battery's energy density.
[0303] The first carbon-based material and / or the second carbon-based material have high capacity advantages. As shown in Table 1, by making the first region of the negative electrode film include both the first carbon-based material and the second carbon-based material, the first carbon-based material has a porous structure and the second carbon-based material includes artificial graphite, the negative electrode sheet can have both high compaction density and low volume change. At the same time, the negative electrode film can also have a reasonable pore distribution, which is conducive to the transport of active ions. Thus, the battery can have high energy density while also taking into account high safety performance, good kinetic performance and cycle performance.
[0304] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
[0305]
[0306]
Claims
1. A secondary battery, comprising a negative electrode, wherein, The negative electrode sheet includes a negative current collector and a negative electrode film layer formed on at least one surface of the negative current collector. The negative electrode film layer has a first surface away from the negative current collector and a second surface disposed opposite to the first surface. The thickness of the negative electrode film layer is denoted as H. The region from the second surface of the negative electrode film layer to a thickness of 0.3 H is denoted as the first region of the negative electrode film layer, and the region from the first surface of the negative electrode film layer to a thickness of 0.3 H is denoted as the second region of the negative electrode film layer. The first region includes a first active material, and the second region includes a second active material. The first active material is a first carbon-based material and a second carbon-based material, and the second active material includes a third carbon-based material; The first carbon-based material has a porous structure. The first carbon-based material includes an outer region and an inner region located inside the outer region. The outer region refers to the region formed by extending 0.25 L from the particle surface of the first carbon-based material into the particle interior, where L refers to the minor axis length of the first carbon-based material particle. The total pore area of the outer region is denoted as S1, and the total pore area of the inner region is denoted as S2, and 1.5 ≤ S2 / S1 ≤ 500. The area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm², and the inner region of the first carbon-based material includes one or more pore structures with an area greater than or equal to 0.15 μm². The second carbon-based material includes artificial graphite, and the surface of the artificial graphite does not have a carbon coating layer; The third carbon-based material includes graphite with a carbon coating on its surface.
2. The secondary battery according to claim 1, wherein, The second carbon-based material includes artificial graphite with secondary particles.
3. The secondary battery according to claim 2, wherein, The proportion of artificial graphite in the secondary particles is greater than or equal to 50% in the second carbon-based material.
4. The secondary battery according to claim 1, wherein, The interlayer spacing of the 002 crystal plane of the second carbon-based material is greater than that of the 002 crystal plane of the first carbon-based material; and / or, the degree of graphitization of the second carbon-based material is less than that of the first carbon-based material.
5. The secondary battery according to claim 1, wherein, The specific capacity of the second carbon-based material is less than that of the first carbon-based material.
6. The secondary battery according to claim 1, wherein, The interlayer spacing of the 002 crystal plane of the second carbon-based material is less than or equal to 0.33600 nm.
7. The secondary battery according to claim 6, wherein, The interlayer spacing of the 002 crystal plane of the second carbon-based material is 0.33571nm-0.33600nm.
8. The secondary battery according to claim 1, wherein, The specific capacity of the second carbon-based material is greater than or equal to 353 mAh / g.
9. The secondary battery according to claim 1, wherein, The specific capacity of the second carbon-based material is 355mAh / g-365mAh / g.
10. The secondary battery according to claim 1, wherein, The second carbon-based material has a powder compaction density of 1.75 g / cm³ under a pressure of 20,000 N. 3 -2.05g / cm 3 .
11. The secondary battery according to claim 1, wherein, The second carbon-based material has a powder compaction density of 1.78 g / cm³ under a pressure of 20,000 N. 3 -2.00g / cm 3 .
12. The secondary battery according to any one of claims 1-11, wherein, The second carbon-based material satisfies at least one of the following: (1) The volume distribution particle size Dv10 of the second carbon-based material is 6μm-12μm; (2) The volume distribution particle size Dv50 of the second carbon-based material is 12.0 μm-22.0 μm; (3) The particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is ≤1.65; (4) The tap density of the second carbon-based material is 0.85 g / cm³. 3 -1.30g / cm 3 ; (5) The specific surface area of the second carbon-based material is 1.0 m². 2 / g-2.9m 2 / g.
13. The secondary battery according to claim 12, wherein, The second carbon-based material satisfies at least one of the following: (1) The volume distribution particle size Dv10 of the second carbon-based material is 6.5 μm-11.5 μm; (2) The volume distribution particle size Dv50 of the second carbon-based material is 13.5 μm-20.5 μm; (3) The particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is 0.90-1.65; (4) The tap density of the second carbon-based material is 0.90 g / cm³. 3 -1.30g / cm 3 ; (5) The specific surface area of the second carbon-based material is 1.2 m². 2 / g-2.5m 2 / g.
14. The secondary battery according to claim 1, wherein, 2 ≤ S2 / S1 ≤ 450.
15. The secondary battery according to claim 1, wherein, The area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.10 μm²; and / or, The internal region of the first carbon-based material includes one or more pore structures with an area of 0.15 μm² to 2.0 μm².
16. The secondary battery according to any one of claims 1-5, wherein, The first carbon-based material satisfies at least one of the following: (1) The specific surface area of the first carbon-based material is 0.7 m². 2 / g-1.8m 2 / g; (2) The volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm; (3) The volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-35.0 μm; (4) The ratio of (Dv90-Dv10) / Dv50 of the first carbon-based material is ≤ 1.50; (5) The compacted density of the first carbon-based material under a pressure of 20,000 N is 1.75 g / cm³. 3 -1.95g / cm 3 ; (6) The tap density of the first carbon-based material is 0.80 g / cm³. 3 -1.50g / cm 3 ; (7) The degree of graphitization of the first carbon-based material is ≥ 93.5%; (8) The OI value of the powder of the first carbon-based material is 8-18; (9) The specific capacity of the first carbon-based material is ≥ 354 mAh / g; (10) In the peak pattern of the X-ray diffraction pattern of the first carbon-based material, there are two diffraction peaks in the range of 2θ between 25.5° and 27.5°. Among the two diffraction peaks, the one with smaller 2θ is recorded as the first peak and the one with larger 2θ is recorded as the second peak.
17. The secondary battery according to claim 16, wherein, The first carbon-based material satisfies at least one of the following: (1) The specific surface area of the first carbon-based material is 0.8 m². 2 / g-1.6m 2 / g; (2) The volume distribution particle size Dv50 of the first carbon-based material is 10.0 μm-20.0 μm; (3) The volume distribution particle size Dv90 of the first carbon-based material is 17.0 μm-32.0 μm; (4) The ratio of (Dv90-Dv10) / Dv50 of the first carbon-based material is 0.7-1.40; (5) The compacted density of the first carbon-based material powder under a pressure of 20000N is 1.80 g / cm³. 3 -1.90g / cm 3 ; (6) The tap density of the first carbon-based material is 0.85 g / cm³. 3 -1.45g / cm 3 ; (7) The degree of graphitization of the first carbon-based material is 93.8%-98%; (8) The OI value of the powder of the first carbon-based material is 8-16; (9) The specific capacity of the first carbon-based material is 354 mAh / g-370 mAh / g; (10) In the peak pattern of the X-ray diffraction pattern of the first carbon-based material, there are two diffraction peaks in the range of 2θ 25.5°-27.5°. Among the two diffraction peaks, the one with smaller 2θ is recorded as the first peak and the one with larger 2θ is recorded as the second peak. The ratio of the peak intensity of the first peak to the peak intensity of the second peak is 10:90 - 40:
60.
18. The secondary battery according to claim 1, wherein, The mass percentage of the first carbon-based material in the first active material is ≥ 20wt%.
19. The secondary battery according to claim 18, wherein, The mass percentage of the first carbon-based material in the first active material is 30wt%-70wt%.
20. The secondary battery according to claim 1, wherein, The third carbon-based material includes graphite with a carbon coating on its surface, and the graphite includes at least one of artificial graphite and natural graphite.
21. The secondary battery according to claim 20, wherein, The third carbon-based material includes artificial graphite, and the artificial graphite includes secondary particles.
22. The secondary battery according to claim 21, wherein, The proportion of secondary particles in the artificial graphite is ≥ 50%.
23. The secondary battery according to claim 1, wherein, The interlayer spacing of the 002 crystal plane of the second carbon-based material is smaller than that of the 002 crystal plane of the third carbon-based material; and / or, the degree of graphitization of the second carbon-based material is greater than that of the third carbon-based material.
24. The secondary battery according to claim 1, wherein, The specific capacity of the second carbon-based material is greater than that of the third carbon-based material.
25. The secondary battery according to claim 1, wherein, The compacted powder density of the second carbon-based material under 20,000 N pressure is greater than that of the third carbon-based material under 20,000 N pressure; and / or, the compacted powder density of the first carbon-based material under 20,000 N pressure is greater than that of the third carbon-based material under 20,000 N pressure.
26. The secondary battery according to claim 1, wherein, The volume distribution particle size Dv50 of the second carbon-based material is greater than the volume distribution particle size Dv50 of the third carbon-based material; and / or, the volume distribution particle size Dv50 of the first carbon-based material is greater than the volume distribution particle size Dv50 of the third carbon-based material.
27. The secondary battery according to any one of claims 1, 20-26, wherein, The third carbon-based material satisfies at least one of the following: (1) The volume distribution particle size Dv50 of the third carbon-based material is 10.0 μm-22.0 μm; (2) The ratio of (Dv90-Dv10) / Dv50 of the third carbon-based material is ≤ 1.65; (3) The OI value of the powder of the third carbon-based material is 2.0-6.5; (4) The compacted density of the third carbon-based material under a pressure of 20,000 N is 1.65 g / cm³. 3 -2.00g / cm 3 ; (5) The tap density of the third carbon-based material is 0.85 g / cm³. 3 -1.25g / cm 3 ; (6) The degree of graphitization of the third carbon-based material is ≤ 96%; (7) The specific surface area of the third carbon-based material is 0.9 m². 2 / g-2.5m 2 / g; (8) The specific capacity of the third carbon-based material is 340mAh / g-360mAh / g.
28. The secondary battery according to claim 27, wherein, The third carbon-based material satisfies at least one of the following: (1) The volume distribution particle size Dv50 of the third carbon-based material is 11.5 μm-20.0 μm; (2) The ratio of (Dv90-Dv10) / Dv50 of the third carbon-based material is 0.90-1.65; (3) The OI value of the powder of the third carbon-based material is 2.0-6.0; (4) The compacted density of the third carbon-based material under a pressure of 20,000 N is 1.68 g / cm³. 3 -1.98g / cm 3 ; (5) The tap density of the third carbon-based material is 0.90 g / cm³. 3 -1.25g / cm 3 ; (6) The degree of graphitization of the third carbon-based material is 90.5%-95.5%; (7) The specific surface area of the third carbon-based material is 0.95 m². 2 / g-2.45m 2 / g; (8) The specific capacity of the third carbon-based material is 345mAh / g-360mAh / g.
29. The secondary battery according to claim 1, wherein, The first region and / or the second region also include silicon-based materials.
30. The secondary battery according to claim 29, wherein, Both the first region and the second region include silicon-based materials, and the mass percentage of the silicon-based materials in the first region is less than or equal to the mass percentage of the silicon-based materials in the second region.
31. The secondary battery according to claim 1, wherein, The intermediate region located between the first region and the second region includes the first active material and / or the second active material.
32. An electrical device comprising a secondary battery as described in any one of claims 1-31.
Citation Information
Patent Citations
Nanocomposite battery electrode particles with changing properties
CN107078287A
Negative electrode having improved fast charging performance and lithium secondary battery
CN114430865A
Negative pole piece, preparation method thereof and lithium secondary battery
CN114759157A
Negative electrode and secondary battery comprising same
CN118355522A
Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2013008526A